Analisis Fungsi Sosial Organisasi Kemasyarakatan pada Pimpinan Anak Cabang Pemuda Batak Bersatu Kecamatan Medan Amplas - Muhammad Iqbal; Randa Putra Kasea Sinaga (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to analyze the social function in the social organization of the chairman of branches, Medan Amplas.This research provides benefits theoretically,it can add material for further study regarding the social function of the United Batak Youth community organization(PBB)in the Branch Leadership(PAC)of Medan Amplas,while academically,it can contribute to universities, faculties and study programs in add study materials,references,sources of knowledge about related research,as well as practically,can provide useful recommendations for the organization in the development and sustainability of their functions internally.This research can provide information regarding what activities are carried out based on the functions implemented and the organization's role in society, especially the people of Medan Amplas.In addition,this research can also provide information on how the community supports and rejects the establishment of the organization.This study uses a research approach with a type or qualitative method.Through research using qualitative methods and written descriptively,Author wants to analyze and find out about the social functions of the study community organization in the PAC PBB,Medan Amplas. Based on the results of the research, the authors found that the PBB also synergized with the village government and also that the PBB did not look religion in carrying out their activities. For during the Christmas event, they invited Muslim friends from PAC PBB.It has been almost 4 years and there have not been a handful of people who refuse to side with the PAC PBB Medan Amplas. As for the activities carried out by the PAC PBB, the community participated in the activity.